2014
DOI: 10.1155/2014/759834
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neural Network Error Measures for Simulation of Slender Marine Structures

Abstract: Training of an artificial neural network (ANN) adjusts the internal weights of the network in order to minimize a predefined error measure. This error measure is given by an error function. Several different error functions are suggested in the literature. However, the far most common measure for regression is the mean square error. This paper looks into the possibility of improving the performance of neural networks by selecting or defining error functions that are tailor-made for a specific objective. A neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…where E is error function, R is number 2, y k is output layer, x n is input layer, W is weights array, t is time (Christiansen et al, 2014).…”
Section: Economics Of Agriculturementioning
confidence: 99%
“…where E is error function, R is number 2, y k is output layer, x n is input layer, W is weights array, t is time (Christiansen et al, 2014).…”
Section: Economics Of Agriculturementioning
confidence: 99%
“…The aim of this study is to show that the ANN presented in Christiansen et al 5 can, in fact, be further optimized and reduced in size. The literature suggests a broad variety of pruning methods for optimizing the ANN architecture, and an overview over various pruning algorithms is given in the survey article of Reed.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach has recently been used by Christiansen et al 4 to reduce the simulation time dramatically when conducting a full fatigue life analysis of a mooring line on a floating platform. The same platform structure has been used in Christiansen et al 5 to investigate the influence of using different error measures or cost functions in the network training, and it was, furthermore, found that the resulting trained network used in that analysis simulated more than two orders of magnitude faster than a corresponding nonlinear numerical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising alternatives to evaluate dynamic responses of marine structures with a significant reduction in computational time is the utilization of hybrid methods combining FEA with Artificial Neural Networks (ANNs) [1][2][3][4][5][6][7]. The basic idea of these methods is to employ the remarkable capacity of learning, generalization, and prediction of neural networks to replace the onerous numerical integration of a time domain dynamic analysis by finite elements method.…”
Section: Introductionmentioning
confidence: 99%
“…Pina et al [2] presented hybrid methods which use dynamic autoregressive models applied to the prediction of risers and mooring lines' top tensions. Christiansen et al [3,4] used a similar hybrid methodology in the prediction of top tensions for the fatigue assessment of a mooring line with a substantial reduction in the total simulation time. Chaves et al [5] studied the application of the hybrid method in the prediction of tension and curvatures in the bend stiffener region of a flexible riser and used these results to perform a fatigue verification.…”
Section: Introductionmentioning
confidence: 99%